Prototype Accounting Information System of Revenue in Kindergarten Permata Bandung - Firdaus, Dony Waluya; Khoerunisa, Bilqis (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research seeks to develop a prototype for a Kindergarten Permata Bandung Revenue Accounting Information System. This investigation focuses on the revenue accounting information system prototype. Flowchart Documents is the initial design for the Accounting Information System of Revenue in Kindergarten Permata Bandung. Flowchart Documents Situation Analysis of New Student Registration at the Permata Kindergarten in Bandung, Indonesia, and Flowchart System is Revenue accounting information for Tk.Permata